"We know what we should be eating, but we don't always do that." How and why people eat the way they do: a qualitative study with rural australians - Nina Van Dyke; Michael Murphy; Eric J. Drinkwater (BMC, 2024)
Abstract Background There is evidence that most people are aware of the importance of healthy eating and have a broad understanding regarding types of food that enhance or detract from health. However, greater health literacy does not always result in healthier eating. Andreasen's Social Marketing Model and Community-Based Social Marketing both posit that, in order to change health behaviours, it is crucial to understand reasons for current behaviours and perceived barriers and benefits to improved behaviours. Limited research has been conducted, however, that explores these issues with general populations. This study aimed to help address this gap in the evidence using a qualitative methodology. Methods Three group discussions were conducted with a total of 23 participants: (1) young women aged 18-24 with no children; (2) women aged 35-45 with primary school aged children; and (3) men aged 35-50 living with a partner and with pre- or primary school aged children. The discussions took place in a regional centre of Victoria, Australia. Transcriptions were thematically analysed using an inductive descriptive approach and with reference to a recent integrated framework of food choice that identified five key interrelated determinants: food- internal factors; food- external factors; personal-state factors; cognitive factors; and sociocultural factors. Results We found that food choice was complex, with all five determinants evident from the discussions. However, the "Social environment" sub-category of "Food-external factors", which included family, work, and social structures, and expectations (or perceived expectations) of family members, colleagues, friends, and others, was particularly prominent. Knowledge that one should practice healthy eating, which falls under the "Cognitive factor" category, while seen as an aspiration by most participants, was often viewed as unrealistic, trumped by the need and/or desire for convenience, a combination of Food-external factor: Social environment and Personal-state factor: Psychological components. Conclusions We found that decisions regarding what, when, and how much to eat are seen as heavily influenced by factors outside the control of the individual. It appears, therefore, that a key to improving people's eating behaviours is to make it easy to eat more healthfully, or at least not much harder than eating poorly.